Experimental studies of prestressed steel-concrete wall girders (Academic journal Industrial Machine Building Civil Engineering, 2022)
To reduce the cost of steel for the installation of load-bearing elements of the wall enclosure made of sandwich panels, it is suggested to use prestressed steel-concrete girders with reduced stiffness of the steel part of the cross-section in one plane instead of girders from the pipe. Thus, the span cross-section will be a U-shaped steel profile filled with concrete. Experimental tests were carried out on eight samples of 3000 mm long girders made of bent channel № 10, size 100x50 mm, with a wall thickness of 3 mm, filled with C20/25 class concrete. The prestressing of the cross-section steel part was carried out by pre-bending the cross-section steel part with jacks and fixing it in this position by filling the inner cavity with concrete. As a result of the implementation of these measures during experimental studies, an increase in bearing capacity up to 31% and stiffness up to 57% was confirmed in the case of preliminary bending of the channel and filling with concrete 1.6 times higher than the height of its shelves. The use of such beams makes it possible to reduce steel consumption by 39%.
Keywords: prestressing; steel-concrete; wall girder; experimental studies